ABO discrepancy due to the para-Bombay phenotype: a case report - Ying Lin; Rongcang Chen; Xingzhong Hu (Journal of Men's Health, 2023)
In this study, we aimed to determine and analyze the genetic differences of the FUT1 and FUT2 genes within an individual exhibiting the Para-Bombay phenotype. Standard serological tests were conducted to analyze the ABO phenotype. The amplification of FUT1 and FUT2 genes was conducted by polymerase chain reaction and amplicons were sequenced. The determination of the ABO genotype was conducted by sequencing exons 1 to 7 of the ABO gene. The Lewis phenotype was defined as Le(a−b+); Despite this, red blood cells (RBCs) did not show signs of A, B and H antigens using the serological method utilized in this study. However, Analyses of sequencing and cloning demonstrated the existence of a FUT1 mutation at position c.658C>T and an inactive allele FUT1*01N.06 (c.551_552delAG). Genetic testing for ABO blood types was subsequently determined to be ABO*B.01/ABO*B.01 (c.297A>G; c.526C>G; c.657C>T; c.703G>A; c.796C>A; c.803G>C; c.930G>A). Heterozygosity for indel and missense mutation within the coding region of FUT1 are likely to be responsible for development of the Para-Bombay phenotype.